Corrosion Monitoring of Sabic Iron in Hydrochloric Acid Solutions using some Azo Compounds – Molecular Dynamics, Chemical and Electrochemical Studies (JOURNAL OF ADVANCES IN CHEMISTRY, 2009)
The corrosion inhibition behaviour of Sabic iron in the absence and in presence of some azo compounds derived from 2, 3-and 2, 7-dihydroxynaphthalene was investigated using weight loss, thermometry and galvanostatic polarizations techniques. It was found that, the inhibition efficiency of these compounds depends on their concentration and chemical structure. The inhibitive action of these azo compounds was discussed in terms of blocking the electrode surface by adsorption of the azo dye molecules through the active centres in their structure. The adsorption process follows Temkin isotherm. The effect of temperature on the rate of corrosion was considered and some activated thermodynamic functions were computed and discussed. Quantum chemical calculations and molecular simulations were further applied to reveal the adsorption structure and explain the experimental results.